The effect of special exercises using rubber ropes to develop special endurance and achieve a 200-meter freestyle swimming - أ.د. عدي طارق أ.د. سهاد قاسم أ.د. مواهب حميد (physical education and sport sciences college for women/ Baghdad University, 2020)
Swimming has now become the focus of attention of specialists, which has led to the search for the best methods and various methods of training, which rely heavily on scientific research and studies, through the use of proper planning and a comprehensive scientific and practical vision in the preparation and training process for this game. Some studies have proven that  The use of training methods has a positive role in the athletic training of the swimmer, provided that these methods are used in the correct way according to the scientific principles of training and with the loads and stresses that serve the specialized activity, i.e. the swimming distance. The study aimed at the follow 1- Preparing exercises using elastic ropes 2- Knowing the effect of elastic rope exercises to develop special endurance and achieve 200m swimming  Free. An experimental design with a tightly controlled heart and post test was used for the pre and post tests, and the research sample was chosen by the intentional method.  Conclusions The researchers put forward a set of the following recommendations, which must be emphasized when training with the help of the means under consideration, the most important of which 1- It is necessary to introduce swimming coaches to the importance of how to use training methods and how to properly use them in the water enviro 2-Emphasis must be placed on providing tools and training means that are consistent with the age and gender of swimmers and the specificity of free swimming when used in training.